Towards a validtime case-based reasoning system - Tanawong, Tawin; Chittayasothorn, Suphamit (My University, 2008)
This paper presents a validtime temporal case-based reasoning system. The system supports the use of validtime on cases. This enables users to consult the case-based system and obtain solutions which are the most up to dated as well as old-time classical ones. Also, the users may ask for solutions which were appropriate during a period of time in the past. The classification of temporal case-based reasoning is discussed. There exists temporal case-based systems based on transaction time but no systems, to our knowledge, are based on the valid time. We then propose the extension of a case-based system using the valid time. The classification of consultation problems into current, sequence and non-sequence problems is discussed. The architecture of the validtime case-based reasoning system is also proposed.
Keywords: Case-based reasoning; Temporal case retrieval; Temporal case-based reasoning; Temporal integrity constraints